A retrospective study of 12, 538 internal conical connection implants focused on the long‐term integrity of implant–abutment complexes. Issue 4 (16th February 2022) - Jin, Xiaoting; Guan, Ye; Ren, Jie; Zhao, Yanwei; Wang, Xiaoxiang; He, Fuming
Abstract: Objective: To evaluate the long‐term integrity of implant–abutment complexes in implant systems with two internal conical angles. Material and Methods: 12, 538 bone‐level implants of two systems placed between January 2012 and December 2018 were retrospectively analyzed. Cumulative abutment/implant fracture rates in systems with larger (LA, 7.5°) and smaller (SA, 5.7°) internal conical angles were estimated using the Kaplan–Meier analysis and compared between groups. The association between implant systems and jammed abutment retrievability was evaluated by multivariable generalized estimating equation logistic regression modeling. Results: For LA, the 8‐year cumulative incident rate was 0.10% (95% confidence interval (CI): 0–0.24%) for implant fracture and 0.26% (95% CI: 0.11%–0.41%) for abutment fracture, demonstrating a significant difference in gender ( p  = .03), implant diameter ( p  = .01), jaw ( p  = .006), and antagonist tooth ( p  < .001). For SA, the 8‐year cumulative incident rate was 0.38% (95% CI: 0–0.79%) for implant fracture and 2.62% (95% CI: 0.05%–5.13%) for abutment fracture, which was influenced by implant diameter ( p  < .001) and site ( p  = .03). The cumulative implant/abutment fracture rate was lower for LA implants, particularly for LA implant‐supported single crowns (SCs) ( p  < .05). The abutment‐retrieval success rate was 92.9% for LA and 57.1% for SA ( p  = .055). Conclusion: LA implants exhibited a lower incidence of fracture in abutment–implant complexes and a relatively higher retrievability success rate for jammed abutments.